2022
DOI: 10.1177/00220027221119768
|View full text |Cite
|
Sign up to set email alerts
|

Inconstant Care: Public Attitudes Towards Force Protection and Civilian Casualties in the United States, United Kingdom, and Israel

Abstract: The choice between protecting friendly soldiers or foreign civilians is a critical strategic dilemma faced in modern war. Prevailing theories suggest that casualties among both groups depress war support in Western democratic societies. Yet we know little about how ordinary citizens balance force protection and civilian casualty avoidance, and whether public opinion differs across Western democracies. Using survey experiments, we test three micro-foundations for what we call individuals’ “harm-transfer prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…War support research has demonstrated that citizens do respond to civilian casualties by decreasing their support for military action (Dill, Sagan, and Valentino 2023). However, research by Johns and Davies (2019) with U.S. and U.K. respondents showed that citizens are much more sensitive to military than civilian casualties.…”
Section: Unanswered Questions Casualtiesmentioning
confidence: 99%
“…War support research has demonstrated that citizens do respond to civilian casualties by decreasing their support for military action (Dill, Sagan, and Valentino 2023). However, research by Johns and Davies (2019) with U.S. and U.K. respondents showed that citizens are much more sensitive to military than civilian casualties.…”
Section: Unanswered Questions Casualtiesmentioning
confidence: 99%